Adjustment problems among international students in Malaysian private higher education institutions - Malaklolunthu, Suseela; Sateyen Selan, Poovaikarasi (Elsevier Ltd., 2011)
The Malaysian government aims to internationalize tertiary education in the country. In order to attract more international students, it is important to understand and develop measures to overcome the various kinds of adjustment problems they face. A quantitative survey using the ‘International Student Problem Inventory’ was conducted on randomly selected international students from five major private higher education institutions in Malaysia. Data analysis revealed that the adjustment problems related to academic, religious, personal, and social adjustment problems were rated high, with financial, and language adjustment problems showing the least impact. Based on the findings, some recommendations are provided to help international students get adjusted to the Malaysian environment and achieve academic success.